Transport characteristics and origins of carbon monoxide and ozone in Hong Kong, South China. Issue 16 (30th August 2013) - Ding, Aijun; Wang, Tao; Fu, Congbin
Abstract: [1] Transport characteristics and origins of carbon monoxide (CO) and ozone (O3 ) transported to Hong Kong were investigated using backward Lagrangian particle dispersion modeling (LPDM) and measurement data collected at a regional background station, Hok Tsui, in South China during 2005–2007. LPDM was conducted using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model (HYSPLIT) driven by Global Data Assimilation System (GDAS) data and emission inventories of CO. The LPDM simulations showed very good performance in characterizing temporal variations in CO on both seasonal and synoptic scales during the 3 years. Based on the LPDM simulations, the seasonal cycles of the source origins and transport age of CO were investigated. Carbon monoxide at the background station was found to originate mainly from the coastal regions in southern China and from eastern China, with averaged transport time of about 1 day and 2–4 days, respectively. The O3 annual maximum in autumn was influenced by regional transport of O3 precursors originating from eastern China, suggesting a strong continental outflow and its regional impacts. Photochemical processes contributed to occurrence of O3 episodes with sharp daytime O3 peaks produced from fresh subregional emissions from Hong Kong and the Pearl River Delta region, mixed with inland continental air. By examining the O3 ‐CO relationship and Lagrangian transport time, the roles of transport and photochemical processes in different seasons at Hok Tsui were also investigated. This study demonstrated unique applications of backward LPDM in observational data analysis as well as in understanding source‐receptor relationships and multiscale transport of CO and O3 . Key Points: Multiscale transport controls seasonal & synoptic variations of CO in Hong Kong LPDM is a unique tool for investigating transport and origins of CO and O3